Pengaruh Corpus Luteum Dan Folikel Dominan Terhadap Kualitas Morfologi Oosit Sapi Bali-Timor - Hermilinda Parera; Victor Lenda (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Improvement of cattle production can be obtained by the application of feed and breeding technology. One of the breeding technologies that are rapidly growing is in vitro fertilization, which is part of In vitro embryo production The source of oocytes influence the success of in vitro embryo production The quality of the oocyte were determined by Ovarian follicular environment and followed the follicular growth that were characterized by the presence of a dominant follicle (DF) and corpus lutem (CL). The purpose of this study was to determine the influe nced of dominant follicles and corpus luteum on oocyte morphology ofBali Timor cattle, that were collected by aspiration method. Oocytes were obtained postmortem from the ovaries of Bali Timor cows slaughtered at an Oeba slaughterhouse Ovarian then class ified into 3 groups : I ) ovarian with CL without DF; (II) ovarian with DF, without CL; and (III) ovarian without both DF and CL. The results showed that the number of oocytes with good quality from group III (12.5%) was higher than group I (9.83%), but no significant differently (P> 0.05). The number of oocytes from group II that showed several layers of cells and has a cytoplasm (good quality) was very low.